The endocannabinoid hydrolysis inhibitor SA-57: Intrinsic antinociceptive effects, augmented morphine-induced antinociception, and attenuated heroin seeking behavior in mice. (1st March 2017) - Wilkerson, Jenny L.; Ghosh, Sudeshna; Mustafa, Mohammed; Abdullah, Rehab A.; Niphakis, Micah J.; Cabrera, Roberto; Maldonado, Rafael L.; Cravatt, Benjamin F.; Lichtman, Aron H.
Abstract: Although opioids are highly efficacious analgesics, their abuse potential and other untoward side effects diminish their therapeutic utility. The addition of non-opioid analgesics offers a promising strategy to reduce required antinociceptive opioid doses that concomitantly reduce opioid-related side effects. Inhibitors of the primary endocannabinoid catabolic enzymes fatty acid amide hydrolase (FAAH) and monoacylglycerol lipase (MAGL) show opioid-sparing effects in preclinical models of pain. As simultaneous inhibition of these enzymes elicits enhanced antinociceptive effects compared with single enzyme inhibition, the present study tested whether the dual FAAH-MAGL inhibitor SA-57 [4-[2-(4-chlorophenyl)ethyl]-1-piperidinecarboxylic acid 2-(methylamino)-2-oxoethyl ester] produces morphine-sparing antinociceptive effects, without major side effects associated with either drug class. SA-57 dose-dependently reversed mechanical allodynia in the constriction injury (CCI) of the sciatic nerve model of neuropathic pain and carrageenan inflammatory pain model. As previously reported, SA-57 was considerably more potent in elevating anandamide (AEA) than 2-arachidonyl glycerol (2-AG) in brain. Its anti-allodynic effects required cannabinoid (CB)1 and CB2 receptors; however, only CB2 receptors were necessary for the anti-edematous effects in the carrageenan assay. Although high doses of SA-57 alone were required to produce antinociception, low doses of this compound, which elevated AEA and did not affect 2-AG brain levels, augmented the antinociceptive effects of morphine, but lacked cannabimimetic side effects. Because of the high abuse liability of opioids and implication of the endocannabinoid system in the reinforcing effects of opioids, the final experiment tested whether SA-57 would alter heroin seeking behavior. Strikingly, SA-57 reduced heroin-reinforced nose poke behavior and the progressive ratio break point for heroin. In conclusion, the results of the present study suggest that inhibition of endocannabinoid degradative enzymes represents a promising therapeutic approach to decrease effective doses of opioids needed for clinical pain control, and may also possess therapeutic potential to reduce opioid abuse. Highlights: SA-57 inhibits fatty acid amide hydrolase and monoacylglycerol lipase. SA-57 reverses allodynia in mouse neuropathic and inflammatory pain models. CB1 and CB2 receptors mediate the antinociceptive effects of SA-57 in the carrageenan model of inflammatory pain. SA-57 enhances morphine-induced antinociception. SA-57 reduces heroin self-administration.